Green Property Tax as an Instrument to Promote Energy Efficiency in Urban Buildings - Dias Bessa, Erik Silvie; Duarte Bertulani, Lucas; Rodrigues Muniz, Pablo (Latin American Journal of Energy Research, 2025)
Brazil’s rapid urbanization, with 87% of its population living in cities, intensifies the demand for public policies aimed at energy efficiency in buildings, a sector responsible for nearly half of national electricity consumption. Within this framework, the Green Property Tax (IPTU Verde) emerges as an extrafiscal mechanism to stimulate sustainable practices; however, its implementation lacks technical standardization and alignment with broader sectoral policies. This qualitative and exploratory study draws on bibliographic review and documentary analysis of municipal regulations (Salvador, Palmas, and Curitiba), focusing on verification criteria, scope of fiscal benefits, and potential impacts. Results reveal heterogeneous approaches: Salvador applies a point-based certification system, Palmas emphasizes solar generation, while Curitiba prioritizes environmental conservation. Identified limitations include verification costs, restricted social reach, and weak monitoring. The study concludes that IPTU Verde holds transformative potential if linked to national technical standards, credit and retrofit programs, and continuous performance assessment mechanisms.